2004
DOI: 10.2223/1238
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intubation procedures at reference pediatric and neonatal intensive care units

Abstract: There was no established routine for intubation procedures in the units studied, and the use of muscle relaxants was not usual. The absence of adequate muscle relaxation is associated with more intubation attempts, difficulties and hypoxemia during the intubation procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…5,7,[11][12][13][14][16][17][18] In relation to the complications after extubation, the main factors considered are traumatic tracheal intubation, accidental extubation, tracheal extubation length of time, tracheal tube's size, tracheal tube traction and friction, and balonet's pressure. 5,6,19,22,25,39,41 The results of this study showed an association between complications after extubation and a bigger number of attempts of intubation (Table 1), but it was not possible to demonstrate the relation between these complications and the length of the mechanical ventilation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…5,7,[11][12][13][14][16][17][18] In relation to the complications after extubation, the main factors considered are traumatic tracheal intubation, accidental extubation, tracheal extubation length of time, tracheal tube's size, tracheal tube traction and friction, and balonet's pressure. 5,6,19,22,25,39,41 The results of this study showed an association between complications after extubation and a bigger number of attempts of intubation (Table 1), but it was not possible to demonstrate the relation between these complications and the length of the mechanical ventilation.…”
Section: Discussionmentioning
confidence: 67%
“…5,6,[35][36][37] Other factors pointed as relevant are the lack of all the material necessary for the procedures, inadequate sedation and analgesia, the lack of pre-oxygenation and ventilation to the patient, traumatic tracheal intubation, and/or various attempts to perform it, incorrect positioning of head and neck, choice of a tracheal tube of improper size, tubes made of improper material. 6,25,35,[37][38][39][40][41] Because this study was conducted in a school hospital, most of the tracheal intubations were performed by resident physicians, who provoked a bigger number of complications, with more attempts of intubation, bradycardia, and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the obvious benefits of modern non-depolarizing muscle relaxants (esmeron, cisatracurium besilate) in comparison with their predecessors, their use is not free of side effects and complications. Due to the relatively recent introduction esmeron the practice of pediatric anesthesiology, there is still no sufficient experience of its application and not adequate [2,5]. Some authors suspect influence of prolonged NM-block on septic complications after surgery [7].…”
Section: W Ith the Development Of Anesthetic Management Requirements mentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Premedication can create optimal conditions which increase the ease of intubation through several means, jaw and vocal cord relaxation via muscle relaxants, pharyngeal and laryngeal reflex suppression with sedation, pain reduction with analgesia, and prevention of reflex bradycardia with the use of vagolytics. 10,[19][20][21][22][23] In 2010, an American Academy of Pediatrics (AAP) clinical report 23 refers to a consensus statement from the International Evidence-Based Group for Neonatal Pain concluding that except for emergent situations, premedication should be used for all endotracheal intubations in newborns. 24 In older pediatric patients, rapid sequence induction has become the Keywords ► intubation ► premedication ► neonatologist ► neonatal intensive care…”
mentioning
confidence: 99%